MENINGKATKAN KUALITAS BIMBINGAN PROPOSAL SKRIPSI PADA PRODI PBSI DAN PGSD MELALUI METODE PEMANDUAN BERPIKIR KRITIS (COGNITIVECOACHING) - Muti'ah, Arju; Suhartiningsih, S (Jurnal Pengembangan Pendidikan, 2011)
Abstract. Aphenomenon indicates that consultation process of the thesis wiriting draft ofIndonesian and Literature Education students is not optimum yet. The problemsare the time consumed for writing the proposal of their thesis draft and theunsatisfying draft quality of the students. The first problem shows that moststudents took relatively longer time, more than 6 months for in fact theyshould have done that within 6 months only. Ideally, students are expected tofinish writing their thesis draft and read to be examined within 6 months. Todeal with this, classroom action research was done. The strategy applied isimplementing Cognitive Coaching was implemented into 3 cycles, which in eachcycle has activities reasing consecus, discussion, controvercial topic,dan problem solving serta writing journals. This method can elevate the qualityof the consultation of thesis draft as it was shown by the improvement ofstudents’ attendance 83,33 percent. Generally students’ activities also improveat level 74,5. Meanwhile, the writing of thesis proposal has also shown goodimrovement from cycle to cycle as 3 proposals (30%) that were presented inseminar are in good quality KataKunci : cognitive coaching,proposal skripsi